STRATEGIC DIGITAL MEDIA PR: INTERACTIVE COMMUNICATION, ONLINE REPUTATION MANAGEMENT, AND CRISIS RESPONSE IN THE AGE OF SOCIAL NETWORKS - Yusupova Zulayxo Abdiraimovna (American Journals Publishing, 2025)
This thesis explores the strategic dimensions of digital media public relations, focusing on interactive communication, online reputation management, and crisis response in the era of social networks. It analyzes how digital platforms have transformed PR from a one-directional messaging function into an interactive, real-time engagement system shaped by audience participation and algorithmic visibility.
Keywords: Digital PR, interactive communication, online reputation, crisis response, social networks, audience engagement.